MARKETING APPROACH TO SOLVING PROBLEMS OF SUSTAINABLE BUSINESS MANAGEMENT (Marketing Journal, 2025)
The article explores solutions to the challenges of ensuring sustainable business development and managing it through the lens of marketing tools. The primary task of achieving sustainable development lies in the efficient use of limited resources to meet 22 set objectives —not only under current conditions but also to secure the future for the next generation. In this context, the authors propose a marketing -based approach to achieving the core goals of ESG (Environmental, Social, and Corporate Governance). The ultimate outcome of sustainable business management should be the level of customer satisfaction.
Keywords: business sustainability; ESG; resources; consumers; enterprises; enterprise requirements; marketing approach